Puzzle Game Learning Media Based on Bookwidgets to Improve Learning Outcomes of Fifth Grade Elementary School Students on Photosynthesis Process Material - I Putu Agus Andika Putra; Basilius Redan Werang; Ketut Herya Darma Utami (Universitas Pendidikan Ganesha, 2025)
Students' learning outcomes on the topic of photosynthesis are still relatively low, partly due to the lack of engaging and interactive learning media. This study aims to develop interactive learning media in the form of a game puzzle based on BookWidgets to improve students' learning outcomes. This is a development research using the ADDIE model, involving 20 fifth-grade elementary school students and one classroom teacher. Data were collected through expert validation questionnaires, practicality questionnaires, and learning outcome tests (pre-test and post-test). The instruments included expert assessment sheets, response questionnaires, and multiple-choice test items. Data were analyzed quantitatively using descriptive statistics for validity and practicality, and paired sample t-tests to assess media effectiveness. The validation results indicated that the media were highly valid, with practicality rated at 100% by the teacher and 86.25% by the students. The t-test for effectiveness showed a significance value of 0.001 (p < 0.05), indicating that the media effectively improved student learning outcomes. Thus, the BookWidgets-based game puzzle media can serve as an attractive, interactive, and technology-integrated learning alternative that supports independent and sustainable learning.